2022
DOI: 10.3389/fgene.2022.1008649
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing analysis of the role of miR-499-5p and SOX6 in chicken skeletal myofiber specification

Abstract: MicroRNAs (miRNAs) might play critical roles in skeletal myofiber specification. In a previous study, we found that chicken miR-499-5p is specifically expressed in slow-twitch muscle and that its potential target gene is SOX6. In this study, we performed RNA sequencing to investigate the effects of SOX6 and miR-499-5p on the modulation and regulation of chicken muscle fiber type and its regulatory mechanism. The expression levels of miR-499-5p and SOX6 demonstrated opposing trends in different skeletal muscles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…MiRNAs are endogenous small noncoding RNAs that have been shown to be involved in various cellular processes, including proliferation, differentiation, migration, invasion, and apoptosis, according to numerous studies [28,29]. Importantly, miRNAs play a pivotal role in the repair of oxidative stress damage to the intestinal barrier [30][31][32]. In our study, miRNA sequencing analysis revealed 21 differentially expressed miRNAs in the intestines of cage-reared ducks compared to those in the traditional breeding group.…”
Section: Discussionmentioning
confidence: 59%
“…MiRNAs are endogenous small noncoding RNAs that have been shown to be involved in various cellular processes, including proliferation, differentiation, migration, invasion, and apoptosis, according to numerous studies [28,29]. Importantly, miRNAs play a pivotal role in the repair of oxidative stress damage to the intestinal barrier [30][31][32]. In our study, miRNA sequencing analysis revealed 21 differentially expressed miRNAs in the intestines of cage-reared ducks compared to those in the traditional breeding group.…”
Section: Discussionmentioning
confidence: 59%
“…These miRNAs target SOX6, a repressor of slow muscle-specific gene expression, and CALM1, a key component of cGMP-PKG and calcium signaling pathways, respectively, to regulate the formation of slow muscle fibers. Recent transcriptome sequencing analysis also confirms this conclusion at the omics level ( Liu et al, 2022 ). One such regulator, miR-499-5p, is a well-known positive regulator for type I muscle fibers across species and has been found to influence muscle fiber type transformation in chickens by targeting multiple genes, including cysteine and glycine protein 3 ( CSRP3 ) and calpain 3 ( CAPN3 ) ( Felício et al, 2013 ).…”
Section: Regulating Factors Of Muscle Fiber Heterogeneitymentioning
confidence: 61%
“…Furthermore, circPTPN4, a recently identified circular RNA, functions as a molecular sponge for miR-499-3p, inhibiting mitochondrial biogenesis and activating the phenotype characteristic of fast-twitch muscles ( Cai et al, 2022 ). Over the past three years, multi-omics sequencing studies focusing on oxidative and glycolytic muscle fibers in poultry have revealed numerous potential regulators ( Liu et al, 2020 ; Wang et al, 2020 ; Ju et al, 2021 ; Liu et al, 2022 ) However, most of these findings require validation at the single-cell level to fully understand their roles and mechanisms in muscle fiber type regulation.…”
Section: Regulating Factors Of Muscle Fiber Heterogeneitymentioning
confidence: 99%
“…Notably, miR-499 has been unvealed to negatively regulate the formation of fast-twitch muscle, inhibited the formation of fast-twitch muscle fibers through repressing the expression of Sox6 (Figure 3) (77). It has been found that the knockout of Sox6 can induce remodeling of muscle fiber types and effectively regulate muscle metabolism (79). Furthermore, deeper exploration has demonstrated that Sox6 directly inhibits the transcription of genes related to slow-twitch muscle fiber by binding to the conserved cis-regulatory elements (46).…”
Section: Regulatory Mechanisms Involved In the Poultry Skeletal Muscl...mentioning
confidence: 99%